Why People With Liver (or hepatic ) Cancer Should Die in Short - Time? - Habibzadeh, Nasim (International Physiology Journal, 2018)
This opinion challenges fatalistic framing of hepatic cancer prognosis. It advocates for nuanced discussion of staging, treatment advances, and supportive care, with clear communication to patients and families.
Keywords: Hepatic Cancer; Liver; Staging; Prognosis; Supportive Care